-2x-3y=15x+12

Simple and best practice solution for -2x-3y=15x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-3y=15x+12 equation:


Simplifying
-2x + -3y = 15x + 12

Reorder the terms:
-2x + -3y = 12 + 15x

Solving
-2x + -3y = 12 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-2x + -15x + -3y = 12 + 15x + -15x

Combine like terms: -2x + -15x = -17x
-17x + -3y = 12 + 15x + -15x

Combine like terms: 15x + -15x = 0
-17x + -3y = 12 + 0
-17x + -3y = 12

Add '3y' to each side of the equation.
-17x + -3y + 3y = 12 + 3y

Combine like terms: -3y + 3y = 0
-17x + 0 = 12 + 3y
-17x = 12 + 3y

Divide each side by '-17'.
x = -0.7058823529 + -0.1764705882y

Simplifying
x = -0.7058823529 + -0.1764705882y

See similar equations:

| 2x-(3-3x)=12 | | (5x+10)(4x-10)= | | x+(12+x)=150 | | -5r-18r-(-16r)=14 | | secx/cosx-tanx/cotx=1 | | (6y-9)=-2y+13(3) | | 3y-14=22-y | | 8x-1=5x-22 | | 19.57=2s+4.61 | | 8v+11-3b=2b+2 | | (13s+7)(6s-18)=0 | | 3/4--1/2 | | 20y+y+4y-22y-2y=6 | | 15-3x=40 | | 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= | | t=3c-2d | | 4n-19n+12n=18 | | 5/6x-1=-7 | | -4.5y=-11.7 | | 2x+3y=10x+11 | | 3x-16-5x=40 | | y=-0.4x-2.1 | | 6*x=1500 | | 16s-4s-12s+3s=15 |

Equations solver categories